2000
DOI: 10.1038/sj.jhh.1000927
|View full text |Cite
|
Sign up to set email alerts
|

β-adrenergic receptor density and function in left ventricular hypertrophy in young essential hypertensives

Abstract: A sympathetic overactivity has been reported in the early stages of essential hypertension and has been involved in the pathogenesis of left ventricular hypertrophy (LVH) in essential hypertension. The state of ␤ 2 -adrenergic receptors as related to the presence of this complication was investigated in a group of 15 essential hypertensive patients and compared to 10 normotensive control subjects. Left ventricular mass index was determined by bidimensional echocardiography. Plasma catecholamine levels were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…Cell-surface expression of β-ARs in RPMVECs was measured by intact cell ligand binding as described previously (Wang et al, 2008; McLean et al, 1999; Calls et al, 2000). RPMVECs were cultured on 12-well plates at a density of 5×10 5 cells/well and infected for 48 h. The RPMVECs were then incubated with the ligand [ 3 H] CGP12177 at a concentration of 20 nM for 2 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Cell-surface expression of β-ARs in RPMVECs was measured by intact cell ligand binding as described previously (Wang et al, 2008; McLean et al, 1999; Calls et al, 2000). RPMVECs were cultured on 12-well plates at a density of 5×10 5 cells/well and infected for 48 h. The RPMVECs were then incubated with the ligand [ 3 H] CGP12177 at a concentration of 20 nM for 2 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Cell-surface expression of ␤-AR and ␣ 1 -AR in neonatal cardiomyocytes was measured by intact cell ligand binding as described previously (McLean et al, 1999;Ricci et al, 1999;Calls et al, 2000) with modifications. Myocytes were cultured on 12-well plates at a density of 5 ϫ 10 5 cells/well and infected for 48 h. The myocytes were then incubated with the ligand [ 3 H]CGP12177 at a concentration of 20 nM for 2 h or with [7-methoxy-3 H]prazosin at a concentration of 10 nM for 90 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The current study also examined the unique and joint effect of ethnicity, gender, and age on b 2 -adrenergic receptors on peripheral blood mononuclear cells. It has been suggested that individual differences in the b-adrenergic receptor may account, in part, for the disparity in the prevalence of hypertension between Blacks and Whites (Bono et al, 1995;Brodde, Stuka, & Demuth, 1985;Brushi, Orlandini, & Pavarini, 1984;Calls et al, 2000;Feldman, Limbird, Nadeau, Roberston, & Wood, 1984). Although not entirely consistent, previous studies of healthy persons and those with diagnosed hypertension have reported independent effects of ethnicity, gender, and age with b 2adrenergic receptor number (B max ), dissociation constant (K d ), and cyclic adenosine monophosphate (AMP) production in response to agonist stimulation (Cases et al, 1991;Halper et al, 1984;Kafka et al, 1979;Mader & Davis, 1989;Michel, Brodde, & Insel, 1990;Mills, Dimsdale, Ziegler, & Nelesen, 1995;Muller, Weller, & Krone, 1994;Trimarco et al, 1983), as well as ethnic-(e.g., Stein, Lang, Singh, He, & Wood, 2000;Watkins, Dimsdale, & Ziegler, 1995) and agerelated (Bertel, Buhler, Kiowski, & Lutold, 1980) differences in beta-adrenergic responsiveness to agonist stimulation.…”
mentioning
confidence: 99%